IDENTIFICATION THE DYNAMICS OF PALEOCLIMATE AND PALEOCEANOGRAPHY DURING LATE PLEISTOCENE â HOLOCENE IN WEST SUMATRA WATERS - Bagas Warno Putra, Andryansah
Climate changes occurs in each earth period, so paleoclimatology has an important role as a foundation in making climate models. The Western waters of Sumatra are in the monsoon wind system and influenced by the Indian Ocean Dipole (IOD) climate phenomenon. The research location is in the West Sumatra Waters, which is located between Sumatra Island and Simeulue Island and geographically located at coordinates 02?40' 511’’ N and 096? 52' 793’’ E. The object of this research is a gravity core sediment with sample code ST-16 which was previously taken by the LIPI Research Team through the Widya Nusantara Expedition in the West Sumatra Waters in 2017. The sample was taken at a depth of 1.115 m below sea level and has a length of 2,21 m. This study aims to reconstruct and determine the dynamics of paleoclimate and paleoceanography in the Late Pleistocene – Holocene in the Western Waters of Sumatra, and to find out its relationship with IOD. The analysis conducted in this study are grain size analysis using 221 samples, X-Ray Fluorescence (XRF) analysis using 221 samples and foraminifera analysis using 27 samples. Grain size analysis is performed to determine the statistical parameters of grain size. XRF analysis was carried out to determine the chemical elements contained in the sample and be used as a proxy for sediment input and weathering intensity which is considered to represent the dominance of IOD. Foraminifera analysis was carried out to determine the name of the genus to species and abundance of foraminifera and it can be used in Modern Analogue Technique (MAT) analysis to determine Sea Surface Temperature and biozonation analysis by conducting constrained clustering. The age limit between Pleistocene and Holocene is marked by the First Appearance Datum (FAD) of Bolliella adamsi at a depth of 192 cm from 1.115 m below sea level. Based on the results of paleoclimate and paleoceanography reconstructions, there are paleoclimate and paleoceanography dynamics that occurred during the Late Pleistocene –Holocene in the West Sumatra Waters. There are 7 climate periods and there are global climate phenomena such as Younger Dryas, Tropical Cooling, Mid Holocene Peak, and 4,2 K event. The climate phenomenon of IOD has a relationship with the dynamics of paleoclimate and paleoceanography in the West Sumatra Waters. Positive IOD dominates the cold climate which is characterized by the decreased rainfall and negative IOD dominates the warm climate which is characterized by the increased rainfall.